PENGARUH MOTIVASI BELAJAR, KECERDASAN EMOSIONAL, DAN PEMBELAJARAN ONLINE TERHADAP PEMAHAMAN AKUNTANSI PADA MAHASISWA AKUNTANSI - Olbaroh Nikida Romadhoni; Wiwik Saraswati; Ika Makherta Sutadji; Hairul Anam (Jurnal GeoEkonomi, 2024)
This research aims to determine the influence of learning motivation, emotional intelligence, and online learning on accounting understanding. Data was collected from this research by distributing questionnaires to respondents which were filled out online. The population used in this research was 66 students who were considered to adequately represent the population studied which was processed using SPSS. The analysis technique used is the multiple linear analysis method. The results of this research show that learning motivation has been proven to have a significantly positive effect on the level of understanding of accounting in accounting students, while emotional intelligence has no effect on understanding of accounting and online learning has no effect on understanding of accounting.